Living at risk: Exploring the psychological effects of childhood food allergy on mothers - Küçük, Elif; Çiçek, Fatih (Allergologia et Immunopathologia, 2025)
Objectives: Food allergy (FA) is a growing public health concern, imposing significant psychosocial burdens on families and necessitating strict allergen avoidance. The unpredictability of severe reactions is associated with increased anxiety, dietary restrictions, and reduced quality of life. Methods: We conducted a cross-sectional study including 77 mothers of children (0–12 years) with FA and 71 mothers of healthy children. Participants completed the Spielberger State-Trait Anxiety Inventory (STAI), Zarit Caregiver Burden Scale (ZCBS), and European Health Impact Scale (EUROHIS-QOL). Statistical analyses compared anxiety, caregiver burden, and quality of life between groups and explored sociodemographic factors. Results: Mothers in the FA group had significantly higher state anxiety (STAI-S) (P < 0.001) and ZCBS scores (P < 0.001) compared to controls. However, trait anxiety (STAI-T) did not differ significantly between groups (P = 0.508). Additionally, mothers of children with FA reported lower EUROHIS-QOL scores (P = 0.009). Low maternal educational levels (P = 0.005) and middle-range income levels (500–1000/month, P = 0.027) were significantly associated with higher anxiety and caregiver burden. Cow’s milk protein allergy (CMPA) specifically increased trait anxiety (P = 0.035) and reduced mothers’ quality of life (P = 0.003). No significant associations were found between anxiety or caregiver burden and anaphylaxis or other allergenic triggers. Conclusion: Food allergy significantly elevates maternal anxiety and caregiving burden, and reduces quality of life, especially in CMPA cases. Sociodemographic factors exacerbate these effects, highlighting the need for comprehensive, multidimensional interventions. Psychological support and broader public awareness initiatives may help alleviate adverse outcomes and improve caregiver well-being.